ANALISIS JANUARY EFFECT pada INDEKS SEKTORAL di PASAR MODAL INDONESIA (STUDI PADA TAHUN 2008-2015) - PUTRA, MOCHAMMAD AKBAR FARRASDIYANTO (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research purposed to analyze is January Effect happened in sectoral indices. January Effect is an anomaly where the stocks return tend to be higher than in other months. The data used in this research is monthly return from each sectoral indices. The metode that used in this research are Independent Sample T Test for parametric data and Mann Whitney U Test for non-parametric data. The result is January Effect does not happened in every sectoral indices. Meanwhile, the fact from the research showing reverse anomaly january effect. Keywords : January Effect, Anomaly, Sektoral Indices